Characteristic of urban wastewater in Hanoi City – nutritive value and potential risk in using for agriculture - Dao, Chu Anh; Con, Pham Manh; Khai, Nguyen Manh (VNU Journal of Science: Earth and Environmental Sciences, 2010)
Abstract . Reusing domestic wastewater for irrigation is a common practice in peri-urban areas in Vietnam. This study investigates the characteristic of domestic wastewater in Hanoi City in terms of nutritive value and potential risk in using for agriculture. The wastewater samples were collected in four main drainage rivers of the City including Lu, Set, Kim Nguu, and To Lich River during March to May 2010. We found that the wastewater of Hanoi City is seriously polluted by organic matters. The nutrient parameters were really high and which is suitable for agricultural irrigation. The wastewater might supply enough nutrients for plant growing. However, municipal wastewater contains a variety of inorganic substances from domestic and industrial sources, including a number of potentially toxic elements such as 1.09-2.14 µg Cd L -1 , 0.16-0.33 mg Cu L -1 , 2.75-4.02 µg Pb L -1 , 0.20-0.34 mg Zn L -1 and 0.22-0.44 mg Mn L -1 . These were also a significant quantities of heavy metals being higher than natural river water, and possible threat to soil biota and hence on microbial and faunal activity, and then human health. Keywords :  heavy metals, irrigation, trace metals, treatment, wastewater.